TRAUMATIC EXPERIENCES AND PSYCHOPATHIC TRAITS IN THE NOVEL HANNIBAL RISING BY THOMAS HARRIS: A PSYCHOLOGICAL STUDY OF THE MAIN CHARACTER - Femy Ramadhina; Agnes Setyowati H; Ni Made Widisanti S (Universitas Pakuan, 2020)
This research’s titled is